The role of hypoxia in oral cancer and potentially malignant disorders: a review. (25th August 2016) - Kujan, Omar; Shearston, Kate; Farah, Camile S.
Abstract : Oral and oropharyngeal cancer are major health problems globally with over 500 000 new cases diagnosed annually. Despite the fact that oral cancer is a preventable disease and has the potential for early detection, the overall survival rate remains at around 50%. Most oral cancer cases are preceded by a group of clinical lesions designated 'potentially malignant disorders'. It is difficult to predict if and when these lesions may transform to malignancy, and in turn it is difficult to agree on appropriate management strategies. Understanding underlying molecular pathways would help in predicting the malignant transformation of oral potentially malignant disorders and ultimately identifying effective methods for early detection and prevention of oral cancer. Reprogramming energy metabolism is an emerging hallmark of cancer that is predominantly controlled by hypoxia‐induced genes regulating angiogenesis, tumour vascularization, invasion, drug resistance and metastasis. This review aims to highlight the role of hypoxia in oral carcinogenesis and to suggest future research implications in this arena.